“HEAVEN IS AS NEAR . . . ”: THE EVOLUTION OF AN ENGLISH PROVERB - Doyle, Charles Clay (Proverbium - Yearbook, 2015)
The proverb “We are as near Heaven by sea as by land,” or “The way to Heaven is the same from all places,” or the formula “Heaven is as close to X as to Y” entered the English language toward the end of the fifteenth century. The proverb—or at least the concept expressed by the proverb—has classical roots. It was famously used in the English Renaissance, and its currency persists into modern times.